2022
DOI: 10.1021/acs.jmedchem.2c01246
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Isoform-Selective Akt3 Degraders Overcoming Osimertinib-Induced Resistance in Non-Small Cell Lung Cancer Cells

Abstract: EGFR inhibitor therapies have brought significant benefit to NSCLC patients. However, all patients gradually progress to acquired resistance via diverse mechanisms. Akt3 overexpression but not Akt1/2 is one of the found molecular events that mediate osimertinib (1) resistance in NSCLC patients. Here, we report 12l as the first bona fide isoform-selective Akt3 degrader which potently induced proteasomal degradation of the target both in vitro and in vivo, whereas its effects on Akt1/2 were minimal. Using 12l as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…The Ubiquitin−proteasome system has been identified as a hydrophobic tag-mediated protein degradation pathway. 37,38 Similarly, we observed that MG-132 and bortezomib were able to substantially rebound PA protein levels affected by 19b with inhibited functions of the 20S proteasome and the 26S proteasome. This suggested that the proteasome pathway is one of the manners of PA protein degradation mediated by Boc 2 −Lys, perhaps owing to the inhibition of both A2 and B1, excessive accumulation of the ubiquitinated complex containing PA protein, and repositioning to autophagy for degradation (path C).…”
Section: ■ Introductionmentioning
confidence: 61%
“…The Ubiquitin−proteasome system has been identified as a hydrophobic tag-mediated protein degradation pathway. 37,38 Similarly, we observed that MG-132 and bortezomib were able to substantially rebound PA protein levels affected by 19b with inhibited functions of the 20S proteasome and the 26S proteasome. This suggested that the proteasome pathway is one of the manners of PA protein degradation mediated by Boc 2 −Lys, perhaps owing to the inhibition of both A2 and B1, excessive accumulation of the ubiquitinated complex containing PA protein, and repositioning to autophagy for degradation (path C).…”
Section: ■ Introductionmentioning
confidence: 61%
“…Recently, Ding et al reported the first example of the isoform-selective Akt3 degraders 12l by connecting the solvent-exposed surface of a new potential allosteric Akt binder XTF-262 to an adamantyl group via computational studies (Figure 6). 81 In the osimertinib-resistant H1975 (H1975OR) NSCLC cells, degrader 12l displayed potent in vitro and in vivo proteasomal degradation of Akt3 and antitumor efficacy, but had no effects on Akt1/2. Moreover, the use of 12l demonstrated that the noncanonical function of Akt3 significantly contributed to the survival of osimertinibresistant H1975OR NSCLC cells.…”
Section: Akt3 Proteinmentioning
confidence: 99%
“…Although significant progress has been achieved in the development of inhibitors targeting specific proteins in the PI3K/AKT/mTOR pathway to treat NSCLC, acquired drug resistance remains inevitable. However, targeted degradation of AKT may help to overcome drug resistance in NSCLC, and may exert long-term pharmacological effects when compared with their inhibition ( 127 , 128 ). PROTACs can control tumour growth and invasion by inducing the ubiquitination and degradation of AKT.…”
Section: Nsclc-related Targets and Treatmentmentioning
confidence: 99%